The Practical Astronomer's Deep-sky Companion - Gilmour, Jess K. (Patrick Moore's practical astronomy series., 2003)
The Practical Astronomer's Deep-sky Companion is an essential item of equipment for deep-sky observers, whether they are interested in imaging or just sightseeing. This large-format full-colour book is designed to be taken out into the field during observing to provide essential detailed, concentrated information for finding and imaging interesting deep-sky objects. Organised by constellation, each spread features the most interesting objects, with images, information, position, locator maps, recommended exposure times for telescopes of various apertures, and much more!